The FY2011-FY2013 Medium-Term Budget. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This letter provides an assessment of recent macroeconomic developments in Benin and an update on the discussions of Fund staff with the Beninese authorities on macroeconomic policies and structural reforms that could form the basis for the authorities' request for a new arrangement under the Extended Credit Facility (ECF). An earlier assessment letter to donors was issued in December 2009 and is available at http://www.imf.org/external/pp/longres.aspx?id=4399.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United States